Analysis of Overhand Serve Ability in Volleyball Game Among Female Players of BKMF Volleyball FIK UNM - Suriah Hanafi; Silatul Rahmi (Universitas Majalengka, 2025)
This research is descriptive research which aims to determine the top serving ability of female BKMF Volleyball FIK UNM players. The population in this study was all 20 BKMF Volleyball FIK UNM female players. Meanwhile, the sample in this study was 20 players selected by total sampling. Data collection techniques were obtained through testing and measuring volleyball service data. The data analysis techniques used are percentage and analysis. The research data obtained data on the percentage of service ability of 20 players or (100%), the very good category was 2 players or (10.0%), the good category was 5 players or (25.0%), the medium category was 11 players or (55.0%), the less than 2 players or (10.0%), and the very less than 0 players or (0%). Thus, it can be concluded that the percentage of final data results on top service ability results in volleyball games for female BKMF Volleyball FIK UNM players is in the Medium category with a percentage of 50.0%.